Effects of interportal error on dose distribution in patients undergoing breath‐holding intensity‐modulated radiotherapy for pancreatic cancer: evaluation of a new treatment planning method. (6th September 2013) - Takakura, Toru; Nakamura, Mitsuhiro; Shibuya, Keiko; Nakata, Manabu; Nakamura, Akira; Yukinori, Matsuo; Shiinoki, Takeshi; Higashimura, Kyoji; Teshima, Teruki; Hiraoka, Masahiro
Abstract : In patients with pancreatic cancer, intensity‐modulated radiotherapy (IMRT) under breath holding facilitates concentration of the radiation dose in the tumor, while sparing the neighboring organs at risk and minimizing interplay effects between movement of the multileaf collimator and motion of the internal structures. Although the breath‐holding technique provides high interportal reproducibility of target position, dosimetric errors caused by interportal breath‐holding positional error have not been reported. Here, we investigated the effects of interportal breath‐holding positional errors on IMRT dose distribution by incorporating interportal positional error into the original treatment plan, using random numbers in ten patients treated for pancreatic cancer. We also developed a treatment planning technique that shortens breath‐holding time without increasing dosimetric quality assurance workload. The key feature of our proposed method is performance of dose calculation using the same optimized fluence map as the original plan, after dose per fraction in the original plan was cut in half and the number of fractions was doubled. Results confirmed that interportal error had a negligible effect on dose distribution over multiple fractions. Variations in the homogeneity index and the dose delivered to 98%, 2%, and 50% of the volume for the planning target volume, and the dose delivered to 1 cc of the volume for the duodenum and stomach were ± 1 %, on average, in comparison with the original plan. The new treatment planning method decreased breath‐holding time by 33%, and differences in dose‐volume metrics between the original and the new treatment plans were within ± 1 % . An additional advantage of our proposed method is that interportal errors can be better averaged out; thus, dose distribution in the proposed method may be closer to the planned dose distribution than with the original plans. PACS number: 87.53.Bn, 87.55.D‐, 87.55.‐x